Analysis of industry trends in the development of the export potential of chemical industry enterprises in the Stavropol region - T. A. Kulagovskaya; T. A. Tolmacheva (Вестник Северо-Кавказского федерального университета, 2022)
The relevance of the research topic is determined by the fact that today the chemical industry organizations of the Stavropol Territory are faced with increased competition in foreign markets. This is because the main export item is low value-added products (mineral fertilizers, synthetic rubbers, ammonia), while the range of imported goods is much wider and is represented by high value-added products. The article analyzes industry trends in the development of the export potential of chemical industry organizations in the Stavropol Territory. Problems are identified and ways of active inclusion of the region in foreign trade processes are considered. The positive results of the functioning of the National Aerosol Cluster in the region are highlighted and business ideas for the chemical industry are proposed, focused on trends, external demand and general market conditions.